Strengthening mentalizing in a depressed mother of an infant with sleep disorders - Georg, Anna; Kreß, Sandra; Taubner, Svenja (Journal of clinical psychology, 2019)
Parent-infant psychotherapy treats parents to reduce infants’ symptoms and strengthen the quality of the parent-infant relationship. However, little is known about the change processes that are set in place in parent-infant psychotherapy and the therapeutic techniques that are most helpful. The aim of this study was to provide a comprehensive description of the course of one treatment with a depressed mother of an 8 months old infant who received focused parent-infant psychotherapy (fPIP), a brief psychological intervention that aims at fostering mentalizing in the parent. This study also aimed at examining the specific interventions that fostered mentalizing in this case. We assessed therapeutic interventions with the fPIP adherence scale and in-session mentalizing with the Reflective Functioning Scale, and we analyzed qualitatively the moments in therapy that were relevant for the treatment focus and during which the mother demonstrated an increase in reflective functioning. We discussed the results with regard to the processes in the course of treatment and the strengths and limitations of fPIP.